A novel method for assessing proximal tibiofibular joint on MR images in patients with knee osteoarthritis. Issue 12 (December 2018) - Chang, J.; Zhu, Z.; Liao, Z.; Meng, T.; Zheng, S.; Cicuttini, F.; Winzenberg, T.; Wluka, A.; Jiang, D.; Han, W.; Ding, C.
Summary: Objectives: To validate a method to measure the morphological parameters of the proximal tibiofibular joint (PTFJ) in patients with knee osteoarthritis (OA). Methods: 408 participants were examined in this cross-sectional subject-based study. We calculated the fibular contacting area of PTFJ (S) and its projection areas onto the horizontal plane (load-bearing area, Sτ), the sagittal plane (lateral stress-bolstering area, Sφ) and the coronal plane (posterior stress-bolstering area, Sυ). Joint space narrowing (JSN) and osteophyte was measured using radiographs. Cartilage defects, bone marrow lesions (BMLs) and cartilage volume were evaluated using magnetic resonance imaging (MRI). Results: The average PTFJ fibular contacting area was 2.4 cm 2 (SD, ±0.7 cm 2 ). Intra-observer and inter-observer reliabilities of measures of PTFJ morphological parameters were excellent (≥0.90). S, Sτ and Sφ were significantly associated with JSN in the medial tibiofemoral compartment (PR: 1.40, 95% CI 1.10–1.78; PR: 1.65, 95% CI 1.25–2.18 and PR: 0.53, 95% CI 0.29–0.97, respectively). There was a significantly positive association between S, Sτ and medial and/or femoral tibial cartilage defects. S, Sτ and Sυ were significantly and positively associated with medial and/or femoral tibial BMLs (PR: 1.36, 95% CI 1.12–1.64; PR: 1.47, 95% CI 1.17–1.83; and PR: 1.39, 95% CI 1.06–1.82, respectively) after adjustment. S and Sτ were significantly and negatively associated with medial tibial cartilage volume. Conclusions: This novel method to assess the morphological parameters of PTFJ in MRI is reproducible. These parameters are associated with knee radiographic and MRI-based OA-related structural abnormalities, suggesting clinical construct validity. Its predictive validity needs to be examined in future longitudinal studies.